A Convenient and Templated Method for the Fabrication of Monodisperse Micrometer Hollow Titania Spheres. (16th July 2013) - Yao, Haibo; Han, Guojun
Abstract : A simple and widely applicable methodology was presented to synthesize monodisperse micrometer hollow titania spheres (HTS) based on the templating method. It was performed by using the preformed poly(styrene-acrylic acid) (PSA) as template spheres which was mixed with tetrabutyltitanate (TBOT) in an ethanol solvent under steam treatment. The HTS which were obtained by the calcination of PSA/TiO2 composite core-shell spheres had a narrow particle size distribution and commendable surface topography characterized by SEM. The calcined HTS at 500°C displayed crystalline reflection peaks that were characteristic to the anatase phase by XRD. Moreover, some key influencing factors including TBOT concentration and reaction time were analyzed. As expected, the diameter of HTS could be readily controlled by altering the size of PSA template spheres. In addition, the approach was also applied to fabricate hollow zirconia spheres and other inorganic spheres.